StopWatch: Pilot study for an Apple Watch application for youth with ADHD. (April 2021) - Leikauf, John E; Correa, Carlos; Bueno, Andrew N; Sempere, Vicente Peris; Williams, Leanne M
Introduction: To address the need for non-pharmacologic, scalable approaches for managing attention-deficit and hyperactivity disorder (ADHD) in young people, we report the results of a study of an application developed for a wearable device (Apple Watch) that was designed to track movement and provide visual and haptic feedback for ADHD. Methods: Six-week, open label pilot study with structured rating scales ADHD and semi-structured qualitative interview. Apple Watch software application given to users that uses actigraphy and graphic interface as well as haptic feedback to provide feedback to users about level of movement during periods of intentional focus. Linear mixed models to estimate trajectories. Results: Thirty-two participants entered the study. This application was associated with improvement in ADHD symptoms over the 6 weeks of the study. We observed an ADHD-Rating Scale change of β = −1.2 units/week (95% CI = −0.56 to −1.88, F = 13.4, P = .0004). Conclusions: These positive clinical outcomes highlight the promise of such wearable applications for ADHD and the need to pursue their further development.